DESIGN OF ANDROID-BASED MUNA LANGUAGE DICTIONARY APPLICATION USING EXTREME PROGRAMMING METHOD - Anasara, Muhamad Fauzil; As’ad, Ihwana; Mude, Muh. Aliyazid (MATICS: Jurnal Ilmu Komputer dan Teknologi Informasi (Journal of Computer Science and Information Technology), 2023)
Muna is one of the languages spoken by the Muna tribe in Southeast Sulawesi, Indonesia, which belongs to the Austronesian language family. Over time, Muna language began to be rarely used. Muna language learning in education also began to be rarely used and there are almost no Muna language lessons anymore, because people prefer to use foreign languages rather than using their own local languages. As a result, many people in the capital of Muna Regency do not understand or know the vocabulary of the Muna language. One way to preserve it is by utilizing existing technology through applications that can help search vocabulary as a substitute for conventional dictionaries that are large in size that can be carried and viewed at any time. Therefore, this research aims to preserve the Muna language through the design of the Muna language dictionary application by applying the Extreme Programming method. Extreme Programming method is a software development approach that emphasizes collaboration, flexibility, and responsiveness to change. The Muna language dictionary application will be designed with various features that make it easier for users to understand and use the Muna regional language. The Muna regional language dictionary application has also been tested using black box testing, where all the features in this application run well and in accordance with what is needed. Index Terms— Muna language, application, dictionary, Extreme programing.